A PROTOTYPE MODEL ON DEVELOPMENT OF WEB-BASED DECISION SUPPORT SYSTEM FOR EMPLOYEE PERFORMANCE ASSESSMENTS WITH SIMPLE ADDITIVE WEIGHTING METHOD - Ramadhan, Muhammad Chezar; Wiratama, Jansen; Permana, Angga Aditya (Universitas Serang Raya, 2023)
The manager or related supervisor performs employee performance assessments to measure the performance and competency of the company's employees. The results of employee assessments can be used to make decisions. Three problems arise in the performance assessment process for PT Tibeta Logistik Indonesia's current employees. The first is that the assessment process is carried out conventionally. So it takes longer, the assessment results can be more objective, and managers or superiors cannot monitor employee performance evaluation results. Based on the literature review, it is known that the Decision Support System is a method that performs assessments more quickly and objectively. Simple Additive Weighting (SAW) is the Decision Support System method for performance assessment. The decision support system will be implemented on a website-based system designed with a prototype model. This research produces a website-based decision support system that can contribute to companies in evaluating employee performance. Before implementation, the decision support system was tested using the User Acceptance Test (UAT) method and obtained very good average results. Then in the comparison between before and after using the system, the results of employee assessments when using the system get superior results in 3 aspects: Integration, security, and ranking. Kata kunci: DSS, Prototipe, SAW, UAT, website.